Diplomasi Indonesia Dalam Mempromosikan â€œWonderfull Indonesiaâ€ Di Asia Tenggara Tahun 2013-2018 - Hermawan, Anggih; Hartati, Anna Yulia (Faculty of Social and Political Sciences - Universitas Wahid Hasyim, 2022)
As an internationally traded and rapidly growing industry, tourism is one of the main categories in the economic sector. For Indonesia, tourism is one of the main sources of foreign exchange earnings and can create jobs and opportunities for further development. Southeast Asia has a lot of tourism potential, namely from tourist objects and attractions which are a form of interconnected activities and facilities. In this case the researcher uses the concept of Public Diplomacy (First track and Second track) as a reference to answer the problems in this study. The main objective in this study was to determine the level of success of Indonesian diplomacy in promoting Wonderful Indonesia in Southeast Asia and the strategy of the Indonesian government in comparing Wonderful Indonesia. The type of research used is qualitative research and the method used for data collection, in-depth information extraction related to the factors that influence the success of Indonesian diplomacy in promoting Wonderful Indonesia in Southeast Asia. The results of the study show that public diplomacy has a very significant influence on the success of Indonesian diplomacy in promoting Wonderful Indonesia.